The Effect of Online Customer Rating and Online Customer Review on Consumer Purchase Decisions Online at Handmadeshoes Surabaya - Shella Yulmaniar; Agus Baktiono; Hepy Octalia Elfa Kolina (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
In this study, the influence of customer rating and customer reviews influenced purchasing decisions at the Handmadeshoes Surabaya Onlinestore. In this study, the author used quantitative research methods and used data generated from questionnaires that had been distributed to consumers of the Handamadeshoes Surabaya Onlinestore at Shopee stores. This study used a sample of 100 respondents from Handamadeshoes Surabaya Onlinestore consumers at Shopee stores. This study uses quantitative methods with validity, reliability, classical assumption test, multiple linear regression, persial test (Test t), simultaneous test (F) and coefficient of determination (D) with SPSS version 25. The results of this study can show that the free variables of Customer rating and Customer Riview have a positive and significant influence on online purchasing decisions. In this study, of course, it can be a reference for sellers to improve the quality of service and develop the quality of their products in order to increase consumer sales in order to get positive ratings and reviews on their products.